Alginate hydrocolloid impregnated zinc paste bandages-an alternative in the management of lymphoedema? - Franz-Josef Schingale; Hugo Partsch (Veins and Lymphatics, 2013)
Several studies have shown an impressive reduction in swelling as a result of compression, and inelastic bandages have become widely accepted as a part of lymphatic decongestive therapy for managing lymphoedema. Lymphoedema bandaging is indicated to reduce swelling, improve limb shape, skinand tissue-condition and to ameliorate symptoms such as discomfort. Compression therapy for lymphoedema is based mainly on the use of inelastic, short-stretch bandages with high compression, usually protecting the skin with polyurethane foam bandages. In this preliminary report it is shown that completely rigid material like zinc paste applied without padding provides a good level of efficacy.